Integration of renewable energy sources in tandem with electrolysis: a technology review for green hydrogen production - Nnabuife, Somtochukwu Godfrey; Hamzat, Abdulhammed K.; Whidborne, James F.; Kuang, Boyu; Jenkins, Karl W. (Elsevier, 2025)
The global shift toward sustainable energy solutions emphasises the urgent need to harness renewable sources for green hydrogen production, presenting a critical opportunity in the transition to a low-carbon economy. Despite its potential, integrating renewable energy with electrolysis to produce green hydrogen faces significant technological and economic challenges, particularly in achieving high efficiency and cost-effectiveness at scale. This review systematically examines the latest advancements in electrolysis technologies—alkaline, proton exchange membrane electrolysis cell (PEMEC), and solid oxide—and explores innovative grid integration and energy storage solutions that enhance the viability of green hydrogen. The study reveals enhanced performance metrics in electrolysis processes and identifies critical factors that influence the operational efficiency and sustainability of green hydrogen production. Key findings demonstrate the potential for substantial reductions in the cost and energy requirements of hydrogen production by optimising electrolyser design and operation. The insights from this research provide a foundational strategy for scaling up green hydrogen as a sustainable energy carrier, contributing to global efforts to reduce greenhouse gas emissions and advance toward carbon neutrality. The integration of these technologies could revolutionise energy systems worldwide, aligning with policy frameworks and market dynamics to foster broader adoption of green hydrogen.
Keywords: 4004 Chemical Engineering; 40 Engineering; 7 Affordable and Clean Energy; 13 Climate Action; 12 Responsible Consumption and Production; Energy; 34 Chemical sciences